2005
DOI: 10.1073/pnas.0502098102
|View full text |Cite
|
Sign up to set email alerts
|

Controlled fabrication of hierarchically branched nanopores, nanotubes, and nanowires

Abstract: Here, we report a generic synthetic approach to rationally design multiply connected and hierarchically branched nanopores inside anodic aluminum oxide templates. By using these nanochannels, we controllably fabricate a large variety of branched nanostructures, far more complex than what exists today. These nanostructures include carbon nanotubes and metallic nanowires having several hierarchical levels of multiple branching. The number and frequency of branching, dimensions, and the overall architecture are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
282
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(283 citation statements)
references
References 29 publications
0
282
1
Order By: Relevance
“…Because the nanochannels of AAO films can be either one-side open or both-side open [30,31,86], the cap structure of AAO-CNTs can be controlled with good uniformity by selecting different types of AAO templates [33,38]. [87][88][89][90][91]. Li et al [87] first synthesized well aligned Y-junction CNTs using an AAO film with Y-branched nanochannels as template.…”
Section: Synthesis Of Cnts By the Aao Template Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the nanochannels of AAO films can be either one-side open or both-side open [30,31,86], the cap structure of AAO-CNTs can be controlled with good uniformity by selecting different types of AAO templates [33,38]. [87][88][89][90][91]. Li et al [87] first synthesized well aligned Y-junction CNTs using an AAO film with Y-branched nanochannels as template.…”
Section: Synthesis Of Cnts By the Aao Template Methodsmentioning
confidence: 99%
“…Li et al [87] first synthesized well aligned Y-junction CNTs using an AAO film with Y-branched nanochannels as template. Meng et al [88,89] reported a method for preparing AAO template with a hierarchically branched structure (as shown in Figure 9). After the initial anodization to form the stem pores, the anodizing voltage was reduced by a factor of 1 n , transforming a linear pore into a multiply branched pore.…”
Section: Synthesis Of Cnts By the Aao Template Methodsmentioning
confidence: 99%
“…Progresses in PAA-LIGA have shown its abilities not only in the synthesis of the traditional high aspect ratio nanomaterials, such as nanorods (Pan, Zeng et al 2000;Lombardi, Cavallotti et al 2007;Xu, Meng et al 2009)and nanowires (Hong, Bae et al 2001;Xu, Zhang et al 2005), but also some unique nanostructures, such as porous metallic nanorods by galvanic exchange reaction (Mohl, Kumar et al 2010), Y-junction nanowires and multiply branched nanomaterials due to its flexibility in the pore structure control according to the principle 1 s V n  , where V s is the anodizing voltage for stem pores and n is the number of branched pores from that stem (Meng, Jung et al 2005;Xu, Meng et al 2009). The combination of NSL and PAA-LIGA has been further developed to create hierarchically ordered nanowire arrays, as schematically shown in Figure 13A (Chong, Zheng et al 2006).…”
Section: Fabrication Of Hierarchically Ordered Nanowire Arrays On Submentioning
confidence: 99%
“…C 60 and CNTs, as novel all-carbon -electron systems, have increasingly invited exploration for preparing their composite films from both fundamental and practical points of view. It is known that clusters of C 60 [118][119][120] and carbon nanostructures [121] can be deposited electrophoretically onto electrodes to form a film.…”
Section: Pure Carbon Thin Films From Fullerene and Cntmentioning
confidence: 99%
“…Shortly after the discovery of CNTs, several growth methods were developed to synthesize different forms of CNTs in a controlled manner, such as arc discharge, [55] pulsed laser deposition, [56] and catalytic CVD (CCVD). [57] For CCVD, there are several specialized versions, such as hot wire, [58] plasma-enhanced, [59] and template [60] CCVD, which are the most commonly utilized techniques today. Among those methods listed above, CCVD techniques show the great advantage that when applied on prepatterned substrates or catalyst particles, well-aligned CNT films similar to the prepatterned template can be made.…”
mentioning
confidence: 99%